"I felt invisible": First nations LGBTIQSB+ young people's experiences with health service provision in Australia. Issue 1 (2nd January 2023) - Spurway, Kim; Sullivan, Corrinne; Leha, John; Trewlynn, William; Briskman, Linda; Soldatic, Karen
Abstract: There is an absence of research into the effectiveness of service provision for First Nations LGBTIQSB+ young people in Australia. To address this gap, interviews were conducted in Australia to highlight young people's perspectives on essential components of service provision. Participants expressed their concerns about the ongoing impact of implicit and explicit settler-colonial heteronormativity and racism on services providing support for young First Nations LGBTIQSB+ peoples. Although set in Australia, this research supports the body of international research. This research has the potential to create policies and practices centered on the voices and needs of First Nations LGBTIQSB+ youth.